2018
DOI: 10.1177/1082013218782368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of premilling treatments on wheat gluten extraction and noodle quality

Abstract: Wheat cultivars were treated by four different treatments and their flours were obtained after milling. The quality of the obtained wheat flours was determined using various quality parameters and it was observed that premilling treatments significantly affect the gluten content, wet and dry gluten yield, gluten index, and water absorption capacity of gluten, respectively. Acid-treated wheat flours of all the four wheat varieties (C-306, Raj-3765, PBW-343, and KW-11) showed lower gluten content and quality, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Generally speaking, the higher the gluten index of the flour, the longer the stability time and the stronger the gluten strength (Oikonomou et al, 2015). Kaushik reported that rheological properties of the dough strongly correlated with the gluten index (Kaushik, Chawla, Kumar, Janghu, & Lohan, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Generally speaking, the higher the gluten index of the flour, the longer the stability time and the stronger the gluten strength (Oikonomou et al, 2015). Kaushik reported that rheological properties of the dough strongly correlated with the gluten index (Kaushik, Chawla, Kumar, Janghu, & Lohan, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The difference in CV peak current was validated using the one-way analysis of variance (ANOVA) followed by a least significant difference test at 95% confidence (Kaushik et al 2018). For the calculation of means and standard error mean (SEM), Microsoft Excel, 2016 (Microsoft Corp., Redmond, WA) was used.…”
Section: Discussionmentioning
confidence: 99%
“…For protein content conversion factor of 6.25 was used. Triplicate samples were analyzed for each parameter 12 After the analysis of engineering properties for ripe and unripe tendu fruits, drying behavior of ripe tendu fruit slices were studied.…”
Section: Proximate Analysis Of Tendu Fruits Proximate Compositionmentioning
confidence: 99%